Programa de cuentos infantiles para fortalecer la competencia se comunica oralmente en su lengua materna en estudiantes de nivel inicial de la Institución Educativa N° 60087 Lucille Gagne Pellerin, Santa Clotilde 2023 - Pinedo Garate, Normita (2024)
The main purpose of the study was to evaluate the children's storytelling program to strengthen the oral communication skills of preschool students at I.E. No. 60087. The study was guided by an evaluative research, with a quasi-experimental design with pre- and post-tests applied to the experimental and control groups. It included a population of 50 preschool students. The results determined a significant difference in the averages of the competence between the experimental group (which received the educational storytelling program) and the control group (which did not). Students in the experimental group showed a higher average (14.52) compared to the average (9.44) of the control group, evidencing a difference of 5.08 points. This finding was supported by hypothesis tests, specifically the non parametric Student's t-test for independent samples, where significant differences were found (p-value < 0.05). The study concluded that the children's storytelling program strengthened the oral communication skills of students in the experimental group at the educational institution studied.